Disrupting the Redox Balance with a Diselenide Drug Delivery System: Synergistic or Antagonistic?. (9th November 2020) - Choi, Yeon Su; Huh, Kang Moo; Shim, Min Suk; Park, In Suh; Cho, Yong‐Yeon; Lee, Joo Young; Lee, Hye Suk; Kang, Han Chang
Abstract: Effective on‐demand release of therapeutics at an intracellular drug supply hub, the cytosol, is among the important steps for successful drug delivery. To improve cytosolic drug release, this study selects diselenide because the bond is cleaved by both glutathione (GSH) and reactive oxygen species (ROS) in the cytosol. Specifically, upon diselenide cleavage, the levels of GSH or ROS are reduced, resulting in decreased or increased cell viability and either the synergistic or antagonistic death of cancer cells with an anticancer drug, respectively, because GSH and ROS trigger two conflicting functions (i.e., antioxidant vs prooxidant activity). Thus, this study designs a diselenide‐based drug carrier to determine which trigger is the major cause of diselenide degradation, how the disrupted balance between GSH and ROS levels influences cell viability and drug efficacy, and whether the combined use of a diselenide drug carrier and a drug has a synergistic or antagonistic effect. Using a multiple diselenide‐containing nanoparticle (MSePCL‐NP), the study shows that diselenide is cleaved to a greater extent by GSH than by ROS; MSePCL‐NP induces a greater decrease in the viability of cancer cells, but not normal cells; a combination of DOX@MSePCL‐NP synergistically kills cancer cells and inhibits tumor growth in vivo. Abstract : Compared to reactive oxygen species (ROS), glutathione is a major player in the degradation of the diselenide drug carrier to induce cytosolic drug release. Diselenide cleavage enhances the reduction in the viability of cancer cells by increasing the scavenging of glutathione, but not ROS, in the cytosol. A combinatorial use of a diselenide drug carrier and an anticancer drug has synergistic anticancer effects in vitro and in vivo.